Building Health Awareness: Analysis of the Relationship between Knowledge and Attitude with BSE Behavior in Public Health Science Students - Martha Chyntia Sirait; Pichayaporn Ratti (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: The purpose of this study was to determine the relationship between knowledge and attitudes with BSE behavior in students of the Public Health Study Program, Jambi University. Methodology: This study used a descriptive analytic research design with a cross sectional approach. The sampling technique used multistage random sampling on 307 students of Public Health by filling in an online questionnaire through a Googleform. The research variables were knowledge, attitudes and BSE behavior which were analyzed using the Chi-square test. Main Findings: Knowledge of female students in the good category is 73 people. Attitudes in the positive category are 52 people, and for BSE behavior in the good category are 68 people. There is no significant relationship between knowledge and BSE behavior, and there is a significant relationship between attitudes and BSE behavior. Novelty/Originality of this study: The results of this research are expected to be useful as material for developing scientific knowledge and to add to the literature on breast cancer itself as well as a study in developing policies regarding the prevention of non-communicable diseases, especially breast cancer in female students.